Integrated development of the agricultural sector, Sierra Leone. The livestock industry - Food and Agriculture Organization of the United Nations; United Nations Development Programme (1971)
Reports on studies of dif. aspects of the livestock industry (excluding poultry) in Sierra Leone, partic. production; marketing & processing of animal products; availability & consumption of meat, milk & their products; training; and research. Includes recommendations regarding each.